THE STRATEGY INVOLVE EFL LEARNER BY WATCHING ENGLISH MOVIE - Intan Sari Aulia; Melinda Susila Rini; Rhoisa Fatikah Romadhona (2025)
This study examines into the usage of movies as a strategic tool to boost English language proficiency among EFL (English as a Foreign Language) learners. The aims of this study is to find out the strategies used in learning English through movie and how to apply them. This Study also given the global relevance of English, efficient approaches that integrate theoretical understanding and practical application are required. Movies, which provide authentic language circumstances and cultural insights, are an engaging medium that enhances key linguistic abilities such as vocabulary acquisition, pronunciation, and listening comprehension. Utilizing a qualitative research approach, data were gathered through semi-structured interviews conducted over WhatsApp with three English majors at an Indonesian institution. The participants, selected for their advanced English skills and consistent usage of movies for learning, described their strategies and experiences. Subtitle-based learning emphasizes vocabulary acquisition through repeated exposure and contextual comprehension, whereas pronunciation-based learning focuses on imitating native speakers' addressing patterns for greater fluency. Participants mentioned problems like foreign terminology and mimicking native accents, but also stressed the motivational and practical benefits of movie-based learning. The study finds that movies are a useful tool for increasing language acquisition and cultural knowledge while encouraging learner autonomy. Personalized strategies, such as actively engaging with subtitles and mimicking language, were proven to significantly enhance speaking skills. This study contributes to the literature on multimedia-assisted language acquisition by emphasizing the necessity of customized strategies for optimizing outcomes. Future research is urged to investigate the long-term effects of movie-based techniques on overall language competency and learner confidence.